The Effect of the Use of Blanket Warmer on the Increase in Body Temperature in Post Op Section Caesarea Patients in the Recovery Room of the Central Surgical Installation of Dr. M.M Dunda Limboto Hospital - Adriyanto Bobihu; Sabirin B. Syukur; Fadli Syamsuddin (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Hypothermia often occurs during Caesarean section surgery due to the effects of anesthesia and room temperature. Therefore, a Blanket Warmer is necessary to increase the patient's body temperature. Objective: To determine the effect of Blanket Warmer use on body temperature increase in post-Caesarean section patients in the Recovery Room of the Central Surgical Installation of Dr. M.M. Dunda Limboto Regional Hospital. This study used a pre-experimental design with a one-group pretest-posttest. Purposive sampling was used to select 23 respondents. This design involved two observations: before and after the experiment. Results: This study showed a p-value of 0.000 (p<0.05), indicating a significant effect, with an average value of 54.62 before and 67.69 after. It can be concluded that the use of a Blanket Warmer has an effect on increasing body temperature in post-Caesarean Section patients. Conclusion: Therefore, the use of a blanket warmer is essential to increase the body temperature of post-Caesarean Section patients who experience hypothermia while in the Recovery Room.